MONITORING OF GEOMECHANICAL PROCESSES OCCURRING IN THE MOUNTAIN MASS OF GOLDEN ORE MINING (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The issues of organizing and carrying out geomechanical monitoring during underground development of deposits are considered. Brief information is given on the developed software and hardware for instrumental assessment of the stress state and properties of the rock mass. A structure is proposed for constructing geomechanical monitoring systems using a set of instrumental, visual and numerical methods for determining the mechanical state of rocks and its changes in structural elements to assess the stability of structural elements of development systems and make technical decisions to ensure the safety of mining operations.